he Influence of Brand Image on Laptop Purchase Decisions Through Brand Trust as Mediation - Aditiyama, Rendra; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This study aims to analyze the effect of brand image on purchasing decisions with brand trust as a mediating variable, with a focus on students of the Faculty of Economics and Business, Muhammadiyah University of Semarang who use X laptop. The research method used a questionnaire with 95 respondents selected using non-probability sampling techniques, specifically convenience sampling. The sample size was determined using the Slovin formula, and the data was analyzed using the Structural Equation Model (SEM -PLS) method using SmartPLS 4.0. The results showed that brand image has a positive and significant influence on purchasing decisions, brand image also has a positive and significant impact on brand trust, brand trust also influences purchasing decisions positively and significantly. Also, brand trust is proven to have a positive and significant influence in mediating the relationship between brand image and purchasing decisions.